2019
DOI: 10.1016/j.jid.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of a Dual ABC Transporter Substrate and NF-κB Inhibitor Blocks Multiple Sources of Cutaneous Inflammation in Mouse Skin

Abstract: Among the molecular signals underlying cutaneous inflammation is the transcription complex NF-kB, its upstream modulators, and cytokines and chemokines that are the downstream proinflammatory effectors. Central to NF-kB activation is IkB kinase (IKK), which phosphorylates IkBa, releasing NF-kB to the nucleus. In a screening of a kinase inhibitor library, we identified two IKK inhibitors that were high-affinity substrates for p-glycoprotein (ABCB1), the multidrug resistance protein known to facilitate transderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…IMQ is known to decrease cAMP and then induce NF-κB phosphorylation 24 . This activation enhances expression of IL-1β, IL-6, TNF-α, and chemokines in keratinocytes 57 . PDE4 inhibitors elevate cellular cAMP by suppressing NF-κB phosphorylation.…”
Section: Discussionmentioning
confidence: 97%
“…IMQ is known to decrease cAMP and then induce NF-κB phosphorylation 24 . This activation enhances expression of IL-1β, IL-6, TNF-α, and chemokines in keratinocytes 57 . PDE4 inhibitors elevate cellular cAMP by suppressing NF-κB phosphorylation.…”
Section: Discussionmentioning
confidence: 97%
“…To ablate the inflammatory response of psoriasis in the skin, the drug penetration into the deeper cutis is important to inhibit immune cell infiltration. 54 We showed that the upregulated cytokine suppression by unfunctionalized and functionalized nanocarriers was comparable. The IVIS and RFL distribution results demonstrated a higher skin uptake of unfunctionalized nanoparticles compared to the targeted nanocarriers.…”
Section: Discussionmentioning
confidence: 79%
“…Using reverse transcription polymerase chain reaction (RT-PCR) we have shown expression of ABCB1, ABCC1, ABCC2 and ABCG2 in ex vivo human skin and in 3D-reconstructed human epidermis models, with ABCB1 and ABCG2 being barely expressed and ABCC1 being with the highest expression level. Functional analysis has shown that MDR1 and MRP1 expressed in the skin facilitate drug transdermal delivery the ABC transporter-mediated mechanism of absorptive transport represents a critical component of the effectiveness of the topical products [38,40]. In a subsequent RT-PCR analysis for the SLC gene family, we have shown expression of SLCO3A1, SLCO2B1, SLC47A2, SLCO4A1 and SLC47A1 in ex vivo human skin model, with SLC47A1 being highly expressed [36].…”
Section: Introductionmentioning
confidence: 80%